M20 Activation Of The Trkb Receptor Pathway Using A Novel Monoclonal Antibody Agonist: Implications For The Treatment Of Huntington's Disease. (17th September 2014) - Carty, N; Schmidt, L; Bursow, G; Schwagarus, T; Graff, C; Damrath, E; Kuhlbrodt, K; Kohler, M; Koeplin, S; Salomon, K; Jäger, S; Gemkow, M; et al.
Abstract : Background: Huntington's disease (HD) is a debilitating neurodegenerative disease marked by a trinucleotide repeat expansion in the huntingtin gene (HTT) that might lead to production of a pathogenic mutant huntingtin protein (mHTT). Recent evidence suggests that alterations in neurotrophin tyrosine kinase receptor signalling pathways contribute to HD pathophysiology. Brain-derived neurotrophic factor (BDNF)-mediated activation of the tyrosine kinase B (TrkB) receptor is a critical component involved in the survival, differentiation and synaptic plasticity of striatal neurons. Reduced levels of BDNF have been previously reported to be observed in both HD post mortem brain tissue and HD mouse models. Furthermore, mHTT has been shown to reduce levels of BDNF in the striatum by inhibiting its gene expression and cortico-striatal trafficking. Aims: In this study, we explore the capacity of novel mouse TrkB agonistic monoclonal antibodies (mAb TrkB agonist) to activate the TrkB receptor signalling pathway in vivo . Methods: The mAb TrkB agonists were tested in vitro to confirm receptor selectivity, efficient binding affinity and functional activity. Subsequently, wild type mice received intrastriatal bolus injections of mAb TrkB agonist at 6 weeks of age and were sacrificed at four different time points post injection. Results: At 30 min post injection, a significant increase in the phosphorylation of TrkB was observed in striatal neurons of mice treated with the mAb TrkB agonist when compared to vehicle treated and non-treated animals. At 4 h post injection, the levels of TrkB phosphorylation were returned to baseline levels. Quantitative western blots were also performed as an orthogonal method to confirm immunohistochemical results. Overall, our findings demonstrate the functional activity of mAb TrkB agonist antibodies in the CNS and establish the potential of an immuotherapeutic approach for restoring aberrant BDNF-TrkB signalling activity in the HD brain.